Korelasi Dinamis Antara Pergerakan Harga Minyak Dunia dan Indeks Harga Saham Sektoral di Bursa Efek Indonesia - Safitri, Yunita Dewi; Robiyanto, Robiyanto (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
Changes in the situation that move very quickly on the commodity market have an impact on financial markets, one of which is the stock market in Indonesia. Therefore this study aims to examine the dynamic correlation between the movement of world oil prices and the Sectoral Stock Price Index listed on the Indonesia Stock Exchange (IDX). The data used is obtained from secondary data in the form of daily closing price data for world oil prices and Sectoral Stock Price Index from January 2017 to June 2020. The analysis technique used is Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroscedasticity (DCC-GARCH), due to previous studies mostly using a static approach. The results of this study show that the DCC-GARCH value between world oil prices (Brent and WTI) and Sectoral Stock Price Index tends to be very weak. A negative dynamic correlation was also found in the Consumer Goods Sector. This research can be a reference for investors who want to invest stocks in Indonesia by looking at the correlation between world oil prices and the Sectoral Stock Price Index.